Development and Validation of a Reverse Phase High Performance Liquid Chromatographic Method for Simultaneous Estimation of Atorvastatin and Fenofibrate in Tablet Dosage Form - B. Akhila; D. Taruni; Dr. J. Gopala Krishna; Dr B.V. Ramana (The Bioscan, 2026)
A simple, fast, accurate, precise, and reproducible reverse phase high performance liquid chromatographic (RP-HPLC) method was developed for the simultaneous estimation of Atorvastatin and Fenofibrate in tablet dosage form.